Dual-ligand-functionalized dodeca-nuclear lanthanide–tungsten-cluster incorporated selenotungstates and fluorescence detection of dipicolinic acid (an anthrax biomarker). Issue 9 (14th April 2023) - Gong, Tiantian; Yang, Sen; Wang, Zixu; Li, Mengyao; Zhang, Siyu; Liu, Jiancai; Chen, Lijuan; Zhao, Junwei
Abstract : A series of rigid–flexible-ligand functionalized lanthanide incorporated ring-shaped selenotungstates were prepared, in which a europium-containing species was employed as a fluorescence sensor to detect an anthrax biomarker with good performance. Abstract : A series of rigid–flexible-ligand functionalized dodeca-nuclear lanthanide–tungsten heterometal cluster incorporated ring-shaped selenotungstates [H2 N(CH3 )2 ]16 Na2 [Ln4 (H2 O)6 (HPZDA)2 (HFMA)2 W8 O21 ][B-α-SeW9 O33 ]4 ·29H2 O [Ln = Ce 3+ (1 ), Pr 3+ (2 ), Nd 3+ (3 ); H2 PZDA = 2, 3-pyrazine dicarboxylic acid, H2 FMA = fumaric acid] and [H2 N(CH3 )2 ]14 Cs2 Na2 [Eu4 (H2 O)6 (HPZDA)2 (HFMA)2 W8 O21 ][B-α-SeW9 O33 ]4 ·30H2 O (4 ) were prepared by a cooperative strategy of rigid and flexible ligands. The polyanion skeletons of 1–4 comprise an inorganic–organic hybrid dodeca-nuclear [Ln4 (H2 O)6 (HPZDA)2 (HFMA)2 W8 O21 ] 14+ heterometallic cluster surrounded by four trivacant Keggin [B-α-SeW9 O33 ] 8− subunits in a rectangle-like arrangement. Based on its fluorescence properties, 4 was used as a fluorescent probe for detecting an anthrax biomarker dipicolinic acid (DPA) with a low limit of detection, and excellent selectivity and anti-interference. The possible fluorescence enhancement mechanism of 4 in the process of detecting DPA may stem from energy transfer from DPA to Eu 3+ ions in 4, which can be confirmed by decay lifetime measurements of 4 in H2 O and D2 O with and without DPA, and a positive signal of the partial substitution of H2 O ligands on Eu 3+ ions by DPA ligands. This work proposes a feasible cooperative strategy of rigid and flexible ligands for constructing new structural types of polyoxometalate hybrids, and also provides some meaningful insights into efficient biomolecule detection by utilizing polyoxometalate-based luminescence materials.